DIFFERENCES OF BIRTH WEIGHT AND ONSET OF ACHOLIC STOOL BETWEEN EXTRAHEPATIC AND INTRAHEPATIC CHOLESTASIS - Setyoboedi, Bagus; Situmorang, Lasmauli; Prihaningtyas, Rendi Aji; Arief, Sjamsul (Indonesian Midwifery and Health Sciences Journal, 2024)
Background: Biliary atresia (extrahepatic cholestasis) and neonatal hepatitis (intrahepatic cholestasis) are two main causes of cholestasis. It is important to distinguish the type of cholestasis for determine management. Patient with intrahepatic cholestasis have birth weight lower than extrahepatic cholestasis. Onset of acholic stool in extrahepatic cholestasis usually appear in 15-30 days of first life. The aim of the study to identify differences of birth weight and onset of acholic stool between the type of cholestasis. Method: A retrospective study on cholestasis children aged under 2 years was conducted at Dr. Soetomo General Academic Hospital from January 2012 to December 2016. A thorough history of birth weight and onset of acholic stool were undertaken. Based on histopatology liver biopsy patients were classified into twogroups: I (extrahepatic cholestasis) and II (intrahepatic cholestasis). Result: Statistical analysis of Mann Whitney U was used with p<0.05 being significant. A total of 84 children were included, 55% were male. 40 children suffered from extrahepatic cholestasis (mean age 4.8 ± 2.6 months old) and 44 children suffered from intrahepatic cholestasis (mean age 2.9 ± SD 3.8 months old). The mean birth weight between extrahepatic and intrahepatic cholestasis were 2813 ± 704 gram vs 2717 ± 577 gram) (p=0.29). The mean onset of acholic stool between extrahepatic and intrahepatic cholestasis were 43.0 ± 60.6 days vs 26.6 ± 39.7 days (p=0.27). Conclusion : There is no difference of birth weight and onset of acholic stool between extrahepatic and intrahepatic cholestasis.